The role of positive thinking in overcoming stress a cognitive-behavioural approach - Diachkova, Olha; Yeremenko, Larysa; Donets, Ivan; Klymenko, Ivan; Kononenko, Anatoliy (Edelweiss Applied Science and Technology, 2024)
This article discusses the role of positive thinking in Cognitive Behavioral Therapy (CBT) for treating psychological disorders. The relevance of the topic is due to the growing use of CBT in psychotherapeutic practice and the need for a better understanding of its effectiveness, including the role of positive thinking. This work highlights the importance of positive thinking in promoting mental health and well-being. It argues that positive thinking is a practical tool for developing adaptive cognitive strategies, rather than an unattainable ideal. In CBT, positive thinking is not just about replacing negative thoughts with positive ones, but is a component of a comprehensive approach to re-evaluating an individual's experience. Such an approach contributes to the formation of a more realistic and adaptive perception of oneself and the world. The main methods and techniques of CBT, including cognitive restructuring and behavioral experiments, utilize positive thinking as a tool for correcting destructive thoughts and behaviors. This article discusses different perspectives on the effectiveness of positive thinking in CBT, weighing the arguments for and against its potential limitations. It contributes to improving an individual's psychological well-being and developing psychological resilience, which enables more effective coping with life challenges and stresses. However, to achieve maximum effectiveness, the application of positive thinking must be closely integrated with a comprehensive treatment strategy that considers the individual needs and characteristics of each client. This approach requires a profound understanding of the mechanisms of cognitive distortions and their impact on a person's emotional state.